Reputation: 390
I was given an assignment to calculate the length of a list using the foldr
Haskell function, so I did these two examples
flength :: [a] -> Int
flength = foldr (\ _ n -> n+1) 0
flength' :: [a] -> Int
flength' l = foldr aux 0 l
where
aux _ n = n+1
Then, as a personal challenge, the professor asked us to use the snd
function and yesterday I came up with this:
flength'' :: [a] -> Int
flength'' = foldr ((+1).(curry snd)) 0
What I want to happen is that this function will turn the head of the list h
and the accumulator 0
into the pair (h,0)
then return 0
and after that apply it to the function (+1)
I expected this to be done recursively, effectively giving me the length of the list at the end.
Instead, I get this error message:
[1 of 1] Compiling Main ( f1.hs, interpreted )
f1.hs:54:24: error:
* No instance for (Num (Int -> Int))
arising from an operator section
(maybe you haven't applied a function to enough arguments?)
* In the first argument of `(.)', namely `(+ 1)'
In the first argument of `foldr', namely `((+ 1) . (curry snd))'
In the expression: foldr ((+ 1) . (curry snd)) 0 xs
Failed, modules loaded: none.
Why is this happening and how can I get this code to work?
Upvotes: 2
Views: 219
Reputation: 105905
Let us lay all our tools in front of us, like a good artisan does:
foldr :: (a -> b -> b) -> b -> [a] -> b
snd :: (a, b) -> b
First, we note that snd
and foldr
do not really fit well. So let's use curry
, just like you did, and add curry snd
to our small tool library:
foldr :: (a -> b -> b) -> b -> [a] -> b
curry snd :: a -> b -> b
This looks very promising. Now we need to add 1
to the result of curry snd
, otherwise we're just writing flip const
. Let's start with a lambda:
\a b -> 1 + curry snd a b
= \a b -> ((+1) . curry snd a) b
We can now shove of b
and end up with
\a -> (+1) . curry snd a
= \a -> (.) (+1) (curry snd a)
= \a -> ((.) (+1)) (curry snd a)
= \a -> (((.) (+1)) . curry snd) a
Now we can eta-reduce a
from both sides too and end up with
(((.) (+1)) . curry snd) = ((+1) . ) . curry snd
Therefore, your third variant would be
flength'' = foldr (((+1) . ) . curry snd) 0
Now, why did you get your error message? You were close with (+1) . curry snd
, but the types don't work out:
(+1) :: Int -> Int
-- v v
(.) :: (b -> c) -> (a -> b ) -> a -> c
curry snd :: t -> (x -> x)
^ ^
But in your case, the b
s in (.)
's signature didn't match. One of them was an Int
, the other was a function.
TL;DR: If you want to write f (g x y)
point-free, write ((f.) . g)
Upvotes: 4